2019
DOI: 10.3390/s19204500
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Sensitivity and Accuracy of Micro/Nano Water Droplets Detection Using Galvanic-Coupled Arrays

Abstract: A moisture sensor has been reported that detects invisibly small water droplets and distinguishes their particle size with high accuracy and high speed. This sensor uses narrow lines of dissimilar metals as electrodes, arranged with gaps of 0.5 to 10 μm. The working principle for this sensor is that it measures the galvanic current generated when a water droplet forms a bridge-like structure between the electrodes. In addition, the surface of the sensor was controlled by using hydrophilic polymer, GL, and hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…The moisture sensor was very fast at showing an output response in comparison to a hygrometer. The calculated relative humidity near the sensor's surface (black line) reached 100% at a point (dew point = 22.5 • C); beyond this point, the response further increased abruptly due to the formation of water droplets [19]. From this observation, it can be said that it was possible to detect minute and relatively gradual changes in humidity with high accuracy and high speed.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The moisture sensor was very fast at showing an output response in comparison to a hygrometer. The calculated relative humidity near the sensor's surface (black line) reached 100% at a point (dew point = 22.5 • C); beyond this point, the response further increased abruptly due to the formation of water droplets [19]. From this observation, it can be said that it was possible to detect minute and relatively gradual changes in humidity with high accuracy and high speed.…”
Section: Resultsmentioning
confidence: 89%
“…With a lower spacing between the electrodes, such as 0.5 µm, the sensor can even detect much smaller water molecules [18]. Further, the sensor's surface [19] and the sensor as a whole can be modified to the actual target [20]. By using these features, this sensor is expected to detect dew condensation with high accuracy at an early stage and is catered to the actual target.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent research works demonstrated the fabrication of a new moisture sensor based on the existence of two dissimilar Au and Al metal electrodes with a comb-like structure that possesses tailored gap size as desired. Whenever a water droplet bridges the two electrodes as a function of dew point condensation, a galvanic response current could be exclusively detected on the sensor surface with excellent sensitivity and reproducibility at a minimum response time of ~20 ms [19][20][21][22][23][24][25][26][27]. This criterion enabled us to beneficially use our MS in many applications, such as (1) accurate spontaneous detection of a tiny amount of water and determination of its droplet size [19][20][21][22][23].…”
Section: Ah =mentioning
confidence: 99%
“…This criterion enabled us to beneficially use our MS in many applications, such as (1) accurate spontaneous detection of a tiny amount of water and determination of its droplet size [19][20][21][22][23]. (2) Improving sensor sensitivity and accuracy for dew condensation detection while changing its surface wettability [24].…”
Section: Ah =mentioning
confidence: 99%